(untitled) (Proceedings of Southern Federal University. Philology, 2014)
Key words: oppositional substitution, opposition, paradigmatic syntax, communicative types of sentences, speech act, pragmatic polysemy, pragmatic transposition. The article deals with the phenomenon of oppositional substitution in morphology and syntax. The author describes two types of oppositional substitution in the sphere of syntax: pragmatic polysemy (neutralization) and functional-semantic transposition. Neutralization takes place when the grammatical form, which is used, loses its own functional meaning and acquires the meaning of its counter-member; in other words, it becomes functionally equivalent with its oppositional counter-member. This type of oppositional reduction is stylistically indifferent (neutral). Transposition takes place in cases where one member of the opposition preserves to a certain extent its original functional meaning alongside the meaning of its counterpart; the two functional meanings are actually combined. This type of oppositional reduction is stylistically marked. Oppositional substitution both in morphology, and in syntax is a manifestation of asymmetric dualism of a language sign. Petina Svetlana Sergeevna - post-graduate student of theory and practice of the English language dpt.